2018
DOI: 10.1111/epi.14490
|View full text |Cite
|
Sign up to set email alerts
|

Increased adverse events associated with antiepileptic drugs in anti–leucine‐rich glioma‐inactivated protein 1 encephalitis

Abstract: Anti-leucine-rich glioma-inactivated protein 1 (LGI1) encephalitis is a rare autoimmune condition presenting mainly as altered mental state, cognitive dysfunction, and seizure. Antiepileptic drugs (AEDs) are usually initiated to control seizures despite their limited efficacy; however, accumulating clinical experience suggests a high incidence of adverse reactions to AEDs in anti-LGI1 encephalitis. We reviewed the medical records of patients who were diagnosed with anti-LGI1 encephalitis to analyze the adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…More importantly, a study reported an unusually high frequency of severe adverse effects from AEDs in this population of patients . Indeed, half of the LGI1 patients studied in a recent report had to change their AED treatment due to adverse cutaneous drug reactions, consisting mainly of maculopapular eruptions . One patient even presented with drug rash accompanied by eosinophilia and systemic symptoms syndrome (DRESS), a potentially fatal dermatologic condition.…”
Section: Main Subtypes Of Ae and Pns Associated With Epilepsymentioning
confidence: 92%
See 3 more Smart Citations
“…More importantly, a study reported an unusually high frequency of severe adverse effects from AEDs in this population of patients . Indeed, half of the LGI1 patients studied in a recent report had to change their AED treatment due to adverse cutaneous drug reactions, consisting mainly of maculopapular eruptions . One patient even presented with drug rash accompanied by eosinophilia and systemic symptoms syndrome (DRESS), a potentially fatal dermatologic condition.…”
Section: Main Subtypes Of Ae and Pns Associated With Epilepsymentioning
confidence: 92%
“…AEDs should be utilized as symptomatic treatment, starting with a single drug, possibly a sodium‐channel blocker (eg, carbamazepine, oxcarbazepine, eslicarbazepine acetate, lamotrigine, or lacosamide) . However, special caution is needed in rapid dosage increase of aromatic AEDs in LGI1‐Ab encephalitis, given the high incidence of cutaneous adverse effects in this population . If the first AED results are ineffective, the adjunct of a second drug with different or multiple mechanisms of action (eg, valproate) is advisable .…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a strong influence of a specific HLA (human leukocyte antigen) haplotype has been shown in anti-LGI1 encephalitis in Koreans [25]. In our report, the patient presented with typical features of anti-LGI1 limbic encephalitis, including cognitive defects, FBDS, hyponatremia, and had a good response to steroids and IVIG instead of antiepileptic therapy [26,27].…”
Section: Case Presentationmentioning
confidence: 51%